EFEKTIVITAS PENYULUHAN OLAI (OLAHAN KEDELAI) TERHADAP FREKUENSI PEMBERIAN MAKANAN TAMBAHAN PADA ANAK BALITA - Ravika ' Prizenia; Juniar ' Ernawaty; Nurul ' Huda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Supplementary feeding is an intervention program for toddler to maintain and improve the nutritional status. The research aim of this research was to determined the effectiveness Counselling Olai (Processed Soybeans) Toward Supplementary Feeding for Toddler. The research was “Quasy experiment” designed by “Non-equavalent control group” were divided into experimental group and control group. The reseach was conducted on toddler have nutritional status BGM in the region Puskesmas Garuda Pekanbaru. The total sampling was 34 children which consists of 17 experimental group and 17 control group, who fit the inclusion criteria and using purposive sampling technique. Measuring instruments were used in the two groups is the observation sheet. The analysis used univariate and bivariate analized by using Wilcoxon and Man Whitney. The result showed there was increase in the supplementary feeding for toddler in the experimental group after being giving conselling olai (processed Soybeans) was effective for increase in supplementary feeding for toddler. The research results expected to improve the quality of supplementary feeding for toddler. Keywords: BGM, supplementary feeding, processed soybeans, counselling